(untitled) (Bangladesh Journal of Botany, 2022)
MYB gene plays an important role in plant growth, development and response to abiotic stress. In the present study, ‘Yatomi Rosa’ grape (Vitis vinifera L.) was used as the test material. Two MYB, VvMYBB1 and VvMYBA3 gene were obtained by homologous cloning, and their subcellular location, different organs, and expression patterns under stress treatment and hormone induction were obtained. VvMYBB1 and VvMYBA3 proteins were located in the nucleus and belonged to nuclear proteins. They were highly expressed in roots and flowers. These genes might have a negative effect on the formation of peel color. VvMYB1 gene and VvMYBA3 gene might play an important role in drought resistance and salt stress resistance. Under the induction of exogenous hormones, relative expression of VvMYBB1 gene was higher than that of VvMYBA3 gene under IAA, ETH, SA and MeJA treatment. Relative expression of VvMYBB1 gene was lower than that of VvMYBA3 gene under 6-BA, GA3 and ABA treatment. It showed that MYB gene played an important role in the development of different organs of grapes, fruit color, and response to abiotic stress and exogenous hormones induction in grape. Bangladesh J. Bot. 51(3): 499-506, 2022 (September)